CEOs raising daughters and female executives. Issue 2 (4th March 2021) - Wang, Xia; Gao, Cencen; Feng, Mingming
ABSTRACT: We explore the relation between CEOs raising daughters and the proportion of female executives in the firm. We find that compared to CEOs without daughters, CEOs with daughters tend to hire more female executives, suggesting that there is a 'daughter effect' in human resource decisions and that raising daughters can improve CEOs' perceptions of gender equality. The improvement in their perceptions is more significant for CEOs who were born in patriarchal regions where the social system is controlled or governed by men. This study suggests an effective way to increase the proportion of female executives based on CEOs' individual characteristics.